Direct power control of grid-connected wound rotor induction machine without rotor position sensors. - Datta, R. (IEEE Transactions on power electronics)
A method is presented for fast response control of the torque and flux of a grid connected wound rotor induction machine fed by back to back connected voltage source inverters on the rotor side. It is based on the measurement of active and reactive power on the grid side where voltages and currents are alternating at fixed frequency. The active and reactive powers are made to track references using hysteresis controllers. The method eliminates the need for rotor position sensing and gives excellent dynamic performance, as shown by simulation and experimental results from a variable speed constant frequency induction generator system. It is also capable of starting on the fly. It is thus an attractive sensorless control method for drive as well as generator applications